2010
DOI: 10.1029/2009jd012702
|View full text |Cite
|
Sign up to set email alerts
|

Photoreductive dissolution of Fe‐containing mineral dust particles in acidic media

Abstract: [1] In this study, the photoreductive dissolution of Fe-containing mineral dust particles in acidic media is investigated. Photolysis experiments were performed using a solar simulator to irradiate acidic mineral dust suspensions prepared from source materials of Inland Saudi sand (IS), Saharan sand (SS) and one commercial sample, Arizona test dust (AZTD). The results show that Fe dissolution is a pH-dependent process, and total Fe solubility decreases with the solution pH increasing. Comparing iron dissoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 74 publications
9
115
1
Order By: Relevance
“…The results reported here are based on long-term Fe dissolution experiments in dusts at low pHs. These are consistent with previous Fe dissolution experiments at similar pH conditions on dust and/or soils at shorter time scale (12 h to 120 h) which showed that Fe dissolution rates in dust or soils are strongly pH dependent and that Fe dissolves faster initially (Spokes et al, 1994;Spokes and Jickells, 1996;Mackie et al, 2005;Cwiertny et al, 2008;Fu et al, 2010).…”
Section: Fe Dissolution Kineticssupporting
confidence: 81%
See 3 more Smart Citations
“…The results reported here are based on long-term Fe dissolution experiments in dusts at low pHs. These are consistent with previous Fe dissolution experiments at similar pH conditions on dust and/or soils at shorter time scale (12 h to 120 h) which showed that Fe dissolution rates in dust or soils are strongly pH dependent and that Fe dissolves faster initially (Spokes et al, 1994;Spokes and Jickells, 1996;Mackie et al, 2005;Cwiertny et al, 2008;Fu et al, 2010).…”
Section: Fe Dissolution Kineticssupporting
confidence: 81%
“…1) as well as others (Spokes et al, 1994(Spokes et al, , 1996Desboeufs et al, 1999Desboeufs et al, , 2005Mackie et al, 2005;Cwiertny et al, 2008;Fu et al, 2010;Deguillaume et al, 2010). We attribute this as the dissolution of highly reactive first Fe pool.…”
Section: Implications and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Mezkhidze et al (2003) have assumed that hematite is an important source for the dissolved iron over the North Pacific, because most of the iron in surface soil of the Gobi deserts is found in the form of hematite (a-Fe 2 O 3 ) (Hseung and Jackson, 1952;Claquin et al, 1999). However, the assumption of hematite as the solely important source for dissolved iron may need to be revisited, as more comprehensive experimental data for chemical specificity of iron-rich dust become available (Cwiertny et al, 2008;Journet et al, 2008;Schroth et al, 2009;Fu et al, 2010). Here, the illite dissolution is also considered for specification of "structural iron", which is trapped in the crystal lattice of aluminosilicate minerals (RS4 in Table 1).…”
Section: Mineral Aerosol Dissolutionmentioning
confidence: 99%